TCP/IP based networking for telemedicine - Ibrahimy, Muhammad Ibn; Motakabber, S. M. A. (International Association of Computer Science and Information Technology Press, 2013)
A prototype customized network based chat and different type of files transfer system have been developed for telemedicine. In brief, this project comprises of two parts: one is chat section and the other is file transfer section. The main function of the chat section is to establish a connection between collar (client) and called parties (server), so they can conversant to each other on real time. On the other hand, the file transfer section establishes a network connection using TCP/IP protocol, so that the client can transfer any type and any size of data files to the server terminal.